Lean construction and sustainability: A review of research trends and implications for the United Nations SDGs - Mochamad Agung Wibowo; Marah Ali Ammar (E3S Web of Conferences)
Lean Construction has emerged as a transformative approach in the construction industry, emphasizing efficiency, waste reduction, and continuous improvement. This review presents a bibliometric analysis of Lean Construction research from the past two decades, focusing on the evolution, core themes, and contributions to sustainable development. Using the Scopus database and VOSviewer, 4,905 documents were analyzed to identify the most relevant keywords, key research trends, and their alignment with the United Nations Sustainable Development Goals (SDGs). The analysis revealed that Lean Construction is closely linked with concepts such as waste management, sustainability, project management, and Building Information Modeling (BIM), underscoring its potential to contribute to SDG 9 (Industry, Innovation, and Infrastructure), SDG 11 (Sustainable Cities and Communities), and SDG 12 (Responsible Consumption and Production). The study also highlights the challenges of global implementation, such as varying construction practices, resistance to change, and limited access to technology in certain regions. Despite these challenges, the integration of Lean principles offers significant opportunities to improve efficiency and sustainability in the construction sector.